2000
DOI: 10.1016/s0300-483x(00)00145-1
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the hsp70 promoter by environmental inorganic and organic chemicals: relationships with cytotoxicity and lipophilicity

Abstract: Stress proteins (heat shock proteins, HSPs) have been proposed as general markers of cellular aggression and their use for environmental monitoring is often suggested. The aim of this work was to study the potency of various environmentally relevant organic and inorganic chemicals to induce the expression of the HSP70 marker. For this purpose, we used an established HeLa cell line containing the chloramphenicol acetyl transferase (CAT) gene under the control of the hsp70 promoter. The screening of three metall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
0
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(51 citation statements)
references
References 35 publications
5
43
0
3
Order By: Relevance
“…A variety of cytotoxic agents including Cd have been shown to up-regulate hsp70, and hsp70 expression has been examined as a potential marker in toxicologic screening for a number of vertebrate species. The most commonly used assays include Northern and Western blots, as well as hsp70 gene promoters linked to reporter genes in transfected cells (4)(5)(6)(7). Although such assays can serve as a rapid and accurate means to assess toxin impact in cultured cells, they are of limited value in assessing toxicity or elucidating mechanisms in intact individuals during development.…”
mentioning
confidence: 99%
“…A variety of cytotoxic agents including Cd have been shown to up-regulate hsp70, and hsp70 expression has been examined as a potential marker in toxicologic screening for a number of vertebrate species. The most commonly used assays include Northern and Western blots, as well as hsp70 gene promoters linked to reporter genes in transfected cells (4)(5)(6)(7). Although such assays can serve as a rapid and accurate means to assess toxin impact in cultured cells, they are of limited value in assessing toxicity or elucidating mechanisms in intact individuals during development.…”
mentioning
confidence: 99%
“…Extensive studies in this field revealed that virtually every other nonthermal stress could induce Hsps [31][32][33]. Owing to their responsiveness to diverse forms of stress, the stress proteins have undergone widespread application in biomonitoring and environmental toxicology [5,[34][35][36][37][38][39][40][41]. As members of the Hsp70 are often the prominent proteins to be expressed following environmental insults, these stress proteins are, therefore, very useful indicators of cellular aggression, and have been used to monitor the impact of environmental factors on various animal species [42][43][44][45] as well as in in vitro models [28,37,41,46,47].…”
Section: Hsp70 In Environmental Monitoringmentioning
confidence: 99%
“…Owing to their responsiveness to diverse forms of stress, the stress proteins have undergone widespread application in biomonitoring and environmental toxicology [5,[34][35][36][37][38][39][40][41]. As members of the Hsp70 are often the prominent proteins to be expressed following environmental insults, these stress proteins are, therefore, very useful indicators of cellular aggression, and have been used to monitor the impact of environmental factors on various animal species [42][43][44][45] as well as in in vitro models [28,37,41,46,47]. Hsp70 is the target molecule or molecule under investigation because it simultaneously takes part in defense, repair, or detoxification machinery of the cell and becomes a direct and specific indicator of cellular stress [30,[48][49][50][51].…”
Section: Hsp70 In Environmental Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its stress responsiveness, HSPA1A expression is a potential marker in toxicological screening (Gupta et al 2010). In fact, human cells carrying an HSPA1A promoter-driven reporter gene have been used to assess the toxicity of heavy metals, organochlorine compounds, and eluates of industrial wastes (Aït-Aïssa et al 2003;Aït-Aïssa et al 2000). However, HeLa cells may not be metabolically competent enough to metabolize PAHs to more toxic metabolites, such as benzo[a]pyrene diolepoxide.…”
Section: Introductionmentioning
confidence: 99%